2013
DOI: 10.1136/bmjopen-2013-003635
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following unintentional injury: a prospective follow-up study

Abstract: Objective: The aim of this study was to predict time off work following unintentional injuries due to accidents leading to hospital admission.Design: Prospective 6-month follow-up study. Setting:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This is similar to a study on severely injured accident victims, which showed that injury severity did not predict the number of days off work at 3 years [22]. Hepp et al [23] posited that the physical condition could play a more important role immediately following the accident (i.e. at baseline) because hospitalization and rehabilitation directly contribute to the time off work, whereas in the longer term, other factors might gain in importance regarding work disability.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is similar to a study on severely injured accident victims, which showed that injury severity did not predict the number of days off work at 3 years [22]. Hepp et al [23] posited that the physical condition could play a more important role immediately following the accident (i.e. at baseline) because hospitalization and rehabilitation directly contribute to the time off work, whereas in the longer term, other factors might gain in importance regarding work disability.…”
Section: Discussionmentioning
confidence: 51%
“…at baseline) because hospitalization and rehabilitation directly contribute to the time off work, whereas in the longer term, other factors might gain in importance regarding work disability. In the longer-term, factors other than the objective physical impairment, such as psychosocial or subjective factors, might be more important prognostic factors for return to work [23].…”
Section: Discussionmentioning
confidence: 98%
“…To reduce loss of follow-up, two reminders were sent to the patients. The rate of non-response was similar to other studies [54], [55]. To reduce the measurement bias, the INTERMED was completed following the recommendations (for details see: http://www.intermedfoundation.org/) and other potential predictors were either administrative data or VAS.…”
Section: Methodsmentioning
confidence: 97%
“…There were nine studies that reported on RTW as the number of days take off, with five that reported on it as a mean with standard deviation. Of these five (48,62,(64)(65)(66), one study (48) measured the outcome at two time points and another (62) reported on two groups of patients. The pooled estimate of effect size was 102.3 (95% CI 29.7,174.9) (I 2 = 99.8%); i.e., participants in the included studies took a mean of 102.3 days or around 3.5 months postdischarge to return to work.…”
Section: B Sick Leaves or Days Offmentioning
confidence: 99%